PENGARUH STRATEGI PEMASARAN TERHADAP PENJUALAN PRODUK AIR MINUM KEMASAN (KASUS PRODUK MERK MURAQUA PT. TIRTASARI FLORAGRATA KECAMATAN SIAK HULU KABUPATEN KAMPAR) - Pranata, Anuar; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The study aims to determine how the influence of marketing strategies to sales in order to achieve the planned sales target PT. Tirtasari Floragrata Siak Hulu District of Kampar and also to know how sales are made.The population in this study is a distributor PT. Tirtasari Floragrata Siak Hulu District of Kampar by sampling a total of 41 distributors by using census method. The research data in the form of primary data by questionnaire sebaga and secondary research instrument in the form of company archives. Analysis of the data used is to use statistical analysis with SPSS.Based on the results of research by the author took a conclusion the influence of marketing strategies to sales at PT. Tirtasari Floragrata Siak Hulu District of Kampar regency of respondents who researched that each have indicator interrelated and berpenagruh positively to penjuala bottled water products PT. Tirtasari Floragrata Siak Hulu District of Kampar regency.Keywords: Marketing Strategy, Sales